Levedura íntegra e derivados do seu processamento em rações para tilápia do Nilo: Aspectos hematológicos e histológicos - Hisano, Hamilton; Dal Pai Silva, Maeli [UNESP]; Barros, Margarida Maria [UNESP]; Pezzato, Luiz Edivaldo [UNESP] (Universidade Estadual de Maringa, 2006)
The effects of inclusion of whole yeast, autolyzed yeast and yeast cell wall on hematological parameters and gut villus perimeter were evaluated in juvenile Nile tilapia, after 80 experimental days. Isoproteic (32.0% DP) and isoenergetic (3200 kcal DE kg -1) practical diets were supplemented with three levels of whole yeast or autolyzed yeast (1.0, 2.0 and 3.0%) and three levels of yeast cell wall (0.1, 0.2 and 0.3%), plus a control diet (with no test microingredients). Red blood cell count, hemoglobin concentration, total plasmatic protein, hematocrit percentage, mean corpuscular volume, mean corpuscular hemoglobin concentration and gut villus perimeter were evaluated. Variations on hematological parameters in animals fed diets with whole yeast; autolyzed yeast and yeast cell wall were observed to be within normal ranges for this species. There was significant influence (p<0.05) of different levels of yeast and derivatives on intestinal villus perimeter. Results showed that experimental period and proposed levels of whole yeast, autolyzed yeast and yeast cell wall do not provide undesirable alterations on standard hematological parameters to Nile tilapia and can be safely used to compound diets for this species. Results also showed that supplement of yeast cell wall provide higher intestinal villus perimeter.
Whole yeast and yeast derivatives in Nile tilapia diets: Hematological and histological aspects.
Keywords: Autolyzed yeast; Oreochromis niloticus; Saccharomyces sp.; Yeast cell wall; hemoglobin; isoprotein; blood analysis; diet supplementation; erythrocyte count; experimental study; hematocrit; histopathology; mean corpuscular hemoglobin; mean corpuscular volume; nonhuman; pisciculture; Tilapia; yeast; Animalia